PENGARUH BAURAN PEMASARAN JASA TERHADAP PROSES PENGAMBILAN KEPUTUSAN DAN KEPUASAN DEBITUR PADA PT. PERMODALAN EKONOMI RAKYAT PROVINSI RIAU (Jurnal Tepak Manajemen Bisnis, 2014)
This study aimed to analyze the effect of marketing mix toward decisions making process and satisfactiondebtor on Capital of Economy the Peopleâs of Riau Province. The instrument used for data collection was aquestionnaire. The study population was all employees of PT Riau Provincial Peopleâs Economic Capital totaling774 people. The sample in this study is based on the use of Taro Yamane formula obtained by 90 people. Analysisusing multiple linear regression analysis.The calculations show that There is no significant effect between the positive and the product purchasedecision, there is a significant and negative influence on purchasing decisions between cost, there is no significanteffect between the positive and the location of the purchase decision, there is no significant effect between thenegative and promotion on purchase decisions, there is no significant effect between the positive and thepurchase decision, there is no significant effect between the positive and the physical facilities of the purchasedecision, there is a significant and positive effect of the process on purchasing decisions, there is no significantinfluence and positive among the products to customer satisfaction, there is no significant effect between thenegative and the cost of consumer satisfaction, there is no significant effect and positive relationship between thelocation of consumer satisfaction, there is no significant effect between the negative and the promotion ofconsumer satisfaction, a significant difference between the positive and the customer satisfaction, there is nosignificant effect between the negative and the physical means to customer satisfaction, there is a significant andpositive effect between customer satisfaction and process towards a significant difference between the positiveand to the satisfaction of the consumer purchase decision on PT. People in the Economic capital of Riau provinceKeywords : Marketing Mix, Purchase Decision, Customer Satisfaction